PENGARUH PEMAHAMAN BUSHU TERHADAP KEMAMPUAN MENGARTIKAN KANJI - Saragih, Febi Ariani; Yulia, Lavitta (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2018)
One of the difficulties of kanji learning is knowing the meaning of the kanji. This is a very vital thing because kanji is basically a symbol of meaning. Bushu is a kanji-forming factor that shows meaning. For this reason, this study wants to know the influence of bushu understanding on the ability to interpret kanji (a combination of kanji). The theory used in the research is the theory of bushu and kanji. This study using ex post facto research with a quantitative approach. The instrument in this study using a test. The test questions that have been made, are used to determine the level of understanding of bushu on interpreting kanji in Japanese education students 2015. The results showed that the average understanding of bushu respondents was 81.2. While the average understanding of bushu in interpreting the respondent's logo is 85.8. Based on the results of simple linear regression analysis, the magnitude of the influence of bushu understanding (X) on the ability to interpreting kanji (Y) is 50.7%. while the remaining 49.3% is influenced by other factors besides understanding bushu (X). The conclusion of the results of this study is there is a strong influence between understanding bushu on the ability to interpret the meaning of kanji.